Exploring the association between social support and anxiety during major public emergencies: a meta-analysis of the COVID-19 pandemic - Liu, Jianmei; Chang, Siyu; Wang, Zhidan; Raja, Fasahat Z. (Frontiers in Public Health, 2024)
Objective The COVID-19 pandemic has prompted a surge in research focusing on mental health issues faced by society, with particular emphasis on the interplay between social support and anxiety. However, the results of these studies have often been controversial. Methods To address this, we conducted a meta-analysis of 104 studies (N = 107,660) to investigate the relationship between anxiety and social support and the potential moderate variables. Results Our meta-analysis revealed a negative correlation between social support and anxiety (r = −0.233). The study also demonstrated the variation in the relationship between social support and anxiety was moderated by cultural area (Q = 14.120, p < 0.05) and phrase of the pandemic (Q = 13.678, p < 0.05). Conclusion The relationship between social support and anxiety can differ across different cultural areas and throughout the phrase of the pandemic. Consequently, we advocate for a nuanced assessment of the role of social support in mitigating public anxiety, taking into account the mediating effects of these factors in the context of major public emergencies.